ETHNIC CHINESE TRADE STRATEGY IN LANGSA - Maulida Maulida; Muhammad Thalal; Reza Idria (The Department of Islamic History and Culture in cooperation with the Center for Islamic History and Culture in Aceh and Malay World Studies (PUSAKA), Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia, 2022)
Before independence, during the Dutch era, ethnic Chinese first appeared in Langsa. Originally from the Toko Rear Area, or Chinatown Area, they are now dispersed around the city on streets such Jenderal Ahmad Yani Street, Aggusalim Street, Teuku Umar Street, Pasar Hugs, and others. The goal of this study was to learn more about the tactics used by ethnic Chinese traders in Langsa as well as the impact of their commerce on the local populace. By merging data from the literature with field research data, this study employs qualitative research. Interviews, documentation, and non-participant observation were the methods employed in this study. Data reduction, data presentation, and data verification are all types of data analysis techniques. The study's findings demonstrate that elements like religion, culture, (tradition and kinship), education, trade structure, and a suitable environment also have an impact on the habits, capital, and work ethic of the Chinese ethnic group in Langsa. This increased, increased, and advanced the ethnic Chinese trade, which had a significant impact on Langsa's trade growth sector. On the other hand, the influence of ethnic Chinese trade on local communities also had a positive effect, such as the lack of competition between Chinese and local traders; rather, the presence of Chinese traders makes local traders feel profitable because they can buy goods at low prices from Chinese stores. The service system is effective and welcoming, the stock is complete, and the newness of the items is assured. Many locals have also found employment in ethnic Chinese stores. A lot of local community activities, including as weddings, funerals, social meetings, and other events are also attended by ethnic Chinese. In addition to trade contacts, relationships with their surroundings are also firmly formed. To this day, the Chinese continue to uphold the ideals of harmony between the ethnic Chinese and the local community by remembering to give food or ampau to the local children when they celebrate festivals like Chinese New Year.